Content Validation Instrument Rating Factors Contributing to Low Back Pain in Sports - Mitsalina, Dinan; Tomoliyus, Tomoliyus; Rahmatullah, Muhammad Imam; Gusdernawati, Aulia; Ali, Masnur (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2021)
The purpose of this study was to test instruments for assessing the causes of back pain in sports. This research method uses evaluation methods. The research subject is a document. The content validity test used in this study is the expert judgment with the Delphi technique. Validation test uses Content Validity Ratio (CVR) which uses three experts.. The results of the study showed that the items and instrument indicators for assessing the causes of sport injuries on the back showed a high CVR value. The conclusion of the assessment instrument that causes back pain sport injury have high fill validity.This research aims to arrange the assessment instrument to the risk factors of back pain in sports.